Ethnomedicinal Study of Plants Used by Newar Community in Sindhupalchowk District, Nepal - Gurung, Manisha (Journal of Plant Resources, 2023)
The information presented in this paper was gathered by field visits in the study area, key informant interview, informal interviews and group discussion with traditional healers and person from different age having knowledge about the plant and plant based remedies. From the study area, it was found that Newar community uses 32 species of plants belonging to 25 families for treating 13 types of ailments. Leaves and roots were the top priority plant part used for different ailments treatments. The Newar community has used plant resources for centuries and is still reliant on them for a living. The study area was discovered to be rich in plant resources and the elderly have extensive knowledge of the use of medicinal plants. However, due to the ease of access to hospitals and modern medical facilities, the younger generation is uninterested in herbal medicine. Many useful plant species are at risk of extinction in this area due to a lack of proper documentation, conservation and cultivation practices. With the introduction of modern and alternative treatment facilities in the district, indigenous traditional knowledge that has been transmitted orally for years is becoming extinct. Because of the preference of peoples of Newar communities for modern medicine and hospital facilities, indigenous knowledge and skills in medicine have become less focused as a result of modernization. As a result, documentation of such knowledge has become an urgent requirement. The documentation of this research is critical for the enhancement and preservation of local people’s traditional knowledge in Indrawati Rural Municipality.